2006
DOI: 10.4067/s0717-95022006000500024
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Thyroxine and Propylthiouracil in Ehrlich Ascitic Tumor Cells

Abstract: The main purpose of this study was to investigate the effect of thyroxine and PTU in ascitic Ehrlich tumor cells. Tumor was implanted in 30 female mice distributed in three groups: treated with PTU, treated with thyroxine and control. Each group received an intraperitoneal injection of neoplastic cells, pre-incubated with sterile solutions of PTU, thyroxine and distilled water, respectively. On the fifth and seventh days after inoculation, animals received an intraperitoneal injection of the respective solutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…The current in vivo study revealed that DADS has a potential antiproliferative and cytotoxicity effect against EAC (a transplantable neoplasia from a malignant epithelium that corresponds to mammary adenocarcinoma) in EAC-bearing female mice. [14,21] This activity was confirmed by a significant decrease in EAC-aliquot volume and total and alive EAC-cell number, and a tremendous increase in dead EAC-cell count and percent as a result of treatment with DADS in comparison to a vehicle. The anti-tumor cytotoxicity of DADS was associated with an improved survival and increased the life span of EAC-bearing mice.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…The current in vivo study revealed that DADS has a potential antiproliferative and cytotoxicity effect against EAC (a transplantable neoplasia from a malignant epithelium that corresponds to mammary adenocarcinoma) in EAC-bearing female mice. [14,21] This activity was confirmed by a significant decrease in EAC-aliquot volume and total and alive EAC-cell number, and a tremendous increase in dead EAC-cell count and percent as a result of treatment with DADS in comparison to a vehicle. The anti-tumor cytotoxicity of DADS was associated with an improved survival and increased the life span of EAC-bearing mice.…”
Section: Discussionmentioning
confidence: 85%
“…[38][39][40] Thus, it should not be excluded that DADS may have anti-angiogenic effects which in turn may have a crucial role in anti-proliferative effects. [15] As suggested by Freitas et al [14] and Senger et al, [41] the production of ascitic extracellular fluid in Ehrlich carcinoma is said to occur due to increased capillary permeability present in the peritoneal cavity. This vascular change occurs due to increased receptor expression for autocrine motility factor (AMF).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Susceptibility of erythrocytes to peroxides was confirmed by the elevated WBC count, reduced hemoglobin and RBC count, as observed in the control group. The constituents of the extracts probably facilitated improvement in hematological parameters by scavenging reactive oxygen species and improving the antioxidant defense system, thus indicating that the extracts exerted haematopoietic protective activity as well as antioxidant property [24,25].…”
Section: Hematological Effects Of the Extractsmentioning
confidence: 99%